METODE PENDIDIKAN ANAK SEKOLAH DASAR DALAM AJARAN ISLAM - Budi Johan; Alvira Febriana; Anita Yulia Safitri; Shupaeroh, Hanna Yasmin; Marsha Atika Putri; Sipaus Sa'adah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Children's education in Islamic teachings is very important to form noble character and morals from the age of elementary school to 7-12 years. This article discusses the method of Islamic education for children elementary school, the role of the family as the main educator, the concept of children's education in the Qur'an and Hadith, methods and approaches to Islamic education, and its relevance in shaping children's character in the modern era. This study uses a type of qualitative research with a literature study approach (library research) to analyze various scientific and religious sources related to children's education in Islam. The results show that Islamic education from the elementary school age, which is 6-12 years old, is very effective in forming the foundation of children's faith, morals, and character, as well as helping them face the challenges of the times. Metode pendidikan anak Sekolah Dasar dalam ajaran Islam sangat penting untuk membentuk karakter dan akhlak mulia sejak usia sekolah dasar 7-12 tahun. Artikel ini membahas metode pendidikan Islam pada anak sekolah dasar, konsep pendidikan anak dalam Al-Qur’an dan Hadits, metode serta pendekatan pendidikan Islam, serta relevansinya dalam membentuk karakter anak di era modern. Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan studi literatur (library research) untuk menganalisis berbagai sumber ilmiah dan keagamaan terkait pendidikan anak dalam Islam. Hasilnya menunjukkan bahwa pendidikan Islam sejak usia sekolah dasar yaitu 6-12 tahun sangat efektif dalam membentuk fondasi keimanan, moral, dan karakter anak, serta membantu mereka menghadapi tantangan zaman.